Numerical Study of Wall Heat Transfer Effects on Flow Separation in a Supersonic Overexpanded Nozzle - Priyadharshini Murugesan; A. R. Srikrishnan; Akram Mohammad; Ratna Kishore Velamati (Energies, 2023)
In this study, numerical simulations have been carried out to analyze the effect of convective heat transfer on flow separation occurring in a DLP-PAR nozzle. Heat transfer coefficient (0, 200 and 1000 w/m2K) was applied to the nozzle wall to incorporate the cooling effect for different gas inlet temperatures ranging from 1000 to 1500 K. The impact of the cooling effect was analyzed based on nozzle wall temperature and wall static pressure. The wall static pressure distribution also characterizes movement of the separation point. For an inlet temperature of 1000 K, a detailed heat transfer study was carried out for four different nozzle pressure ratios (14, 22, 30 and 40). Significant amount of heat transfer was observed for pressure ratio 14, which in turn had an impact on flow separation. The wall cooling resulted in a shift of the point of separation towards the nozzle exit. For the nozzle pressure ratio of 14, this shift was by about 8.8%, indicating that the flow separation can be delayed by way of cooling for the considered inlet temperature. For higher inlet temperatures, the effect of heat transfer on flow separation seems to be negligible. The current study concludes that the separation point can be controlled by convective cooling for inlet gas temperatures below 1500 K so that the optimal performance of the nozzle can be achieved.